MODELING OF DIGITALIZATION AND VISUALIZATION OF LABOR COMPLAINTS USING OCR, FEATURE EXTRACTION AND BUSINESS INTELLIGENCE - Yan Puspitarani; Sukenda Sukenda; Ari Purno Wahyu; Benny Yustim; Sunjana Sunjana (Jurnal Ilmiah Teknologi Infomasi Terapan, 2021)
The handling of labor complaints is one of the performance factors for Disnakertrans. This performance is related to the decisions that must be taken to determine policies so that violations of labor norms can be reduced. Making this decision will be easier if the data on complaints can be recapitulated quickly and accurately. This recapitulation will be a tool to monitor the leadership in seeing the progress report on the status of incoming complaints. However, the manual administrative process makes the recapitulation slower. Therefore, this study will model the complaint reporting digitization system by utilizing OCR and information extraction as well as modeling the visualization of the results of the recapitulation using Business Intelligence. With the creation of this model, it is hoped that the performance of Disnakertrans in resolving labor complaints will be more effective